Exploring the Relationship Between Frequency Use of Web 2.0 and Meaningful Learning Attributes - Hamdan, Analisa; Din, Rosseni; Abdul Manaf, Siti Zuraida; Mat Salleh, Nor Syazwani; Kamsin, Intan Farahana; Ismail, Nor Mohamad (Journal of Technical Education and Training, 2015)
The education system around the world emphasises the importance of pedagogical innovation using the latest technological advances in order to create effective and meaningful learning. Nevertheless, the studies related to the relationship between Web 2.0 technologies and meaningful learning attributes are inadequate. The objective of the study was to identify the relationship between frequency of Web 2.0 tools and five meaningful learning attributes. Based on a survey with 70 respondents, frequencies of five types of Web 2.0 applications (Facebook, YouTube, WordPress, Twitter and Prezi) that were used as hybrid e-learning tools were identified. Data was collected using a set of instruments. Results show that the instrument is highly reliable and validated. On the other hand, the Web 2.0 technologies had affected positively towards cooperative learning followed by authentic, intentional, and constructive learning. There was no relationship between Web 2.0 and active learning; however, Web 2.0 has been identified to promote active learning. Thus, Web 2.0 tools were found to be able to support teaching and learning process in order to achieve meaningful learning. The use of Web 2.0 will produce high implications in education in order to make sure students achieve meaningful learning at the end of the learning session. Thus, the teaching quality of academicians would be improved and students’ learning achievement would increase. Therefore, advanced research on several types of Web 2.0 applications applied in teaching and learning should be done to achieve meaningful learning.